2015
DOI: 10.1002/cm.21213
|View full text |Cite
|
Sign up to set email alerts
|

Myosin motor isoforms direct specification of actomyosin function by tropomyosins

Abstract: Myosins and tropomyosins represent two cytoskeletal proteins that often work together with actin filaments in contractile and motile cellular processes. While the specialized role of tropomyosin in striated muscle myosin-II regulation is well characterized, its role in non-muscle myosin regulation is poorly understood. We previously showed that fission yeast tropomyosin (Cdc8p) positively regulates myosin-II (Myo2p) and myosin-V (Myo52p) motors. To understand the broader implications of this regulation we exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 72 publications
2
17
1
Order By: Relevance
“… Our results with skeletal myosin II differ from those of Clayton et al () who reported that Tpm3.1 inhibits skeletal myosin II in a gliding assay. After extensive discussion and testing of each other's tropomyosin preparations we concluded the difference is due to the preparation of the gliding surface.…”
contrasting
confidence: 99%
“… Our results with skeletal myosin II differ from those of Clayton et al () who reported that Tpm3.1 inhibits skeletal myosin II in a gliding assay. After extensive discussion and testing of each other's tropomyosin preparations we concluded the difference is due to the preparation of the gliding surface.…”
contrasting
confidence: 99%
“…This therefore may explain why anti‐Tpm3.1 drugs do not phenocopy all effects of genetic deletion. Tpm3.1 recruits myosin II motors to actin filaments (Bryce et al, ; Clayton et al, ; Gateva et al, ; Schevzov et al, ) and elongated mesenchymal invasion requires inhibition of myosin II motor activity at the cell's leading edge (Asokan et al, ). Thus, continued association of Tpm3.1 with actin filaments following exposure to anti‐Tpm3.1 drugs may maintain myosin II activity at the leading edge and thereby block induction of mesenchymal invasion.…”
Section: Discussionmentioning
confidence: 99%
“…There are over 40 tropomyosin isoforms generated through differential transcript splicing from four coding genes (Gunning et al, ). Their major function is to regulate the dynamics of the associated actin filament, via regulating access of different myosin motors (Bryce et al, ; Clayton et al, ; Manstein, & Mulvihilll, ; Schevzov et al, ). Tpm3.1 stabilises actin filaments, through myosin II recruitment (Bryce et al, ; Clayton, Pollard, Murray, & Lord, 2015; Gateva et al, ; Schevzov et al, ) and this stabilising function underpins the multiplicity of roles that have been ascribed to this ubiquitously expressed protein (Bach et al, 2009; ; Bryce et al, ; Caldwell et al, ; Clayton et al, ; Lees, Bach, Bradbury, Lees et al, , 2013; Lim et al, ; Schevzov et al, ; Vlahovich et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Tropomyosins family has long been known for its properties in the construction of cell skeleton, but it actually has shown more functions in others cell processes, such as the pathogenesis of various tumours . It is well known that the most of gene expression could be inhibited during DNA methylation.…”
Section: Discussionmentioning
confidence: 99%